Co-Relation of HBA1C Level with Diabetic Retinopathy on Fundoscopy in Patients Suffering from Type-II DM for more than 10 years Duration - Syed Anees Ahmed Gardezi, Najmusaqib Khan Niazi, Syed Haider Tirmizi, Iffat Rafique, Rabia Sadiq, Muneeb Ur Rehman, Talha Laique, (Pakistan Journal of Medical & Health Sciences, 2022)
Defects in insulin secretion or its metabolic functionality results in increased levels of glucose causing metabolic disorders. Aims: To check the Co- relation of HbA1c level with diabetic retinopathy on fundoscopy in patients suffering from Type II DM for more than 10 years duration. Study Design: Cross sectional study. Methodology: Patients (n=61) who were diagnosed cases of diabetes mellitus type II according to American diabetes association guidelines for the past 10 years were included into the study. HbA1c was assessed on autoanalyzer from Roche and NGSP certified using turbidimetric inhibition immunoassay (TINIA) method of hemolyzed blood samples. Eye examination of patients were carried out by expert ophthalmologist after proper pupillary dialatation was carried out. After proper fundoscopy patients were classified into four stages of diabetic retinopathy based on ETDRS levels. Statistical analysis: Data was analyzed using SPSS version 26. Results were presented as frequency and percentage. Age was presented as mean± SD. Results: Out of 61 patients 38 (62.3%) were male and 23 (37.7%) were female. HbA1c levels and diabetic retinopathy showed a statistically significant association when assessed using chi square test (p=0.001). Comparison of HbA1c levels among various groups based on diabetic retinopathy grading revealed a statistically significant difference (p=0.001). Conclusion: It was concluded that HbA1c levels and diabetic retinopathy were significantly associated. Higher levels of HbA1c which reflected the poor glycemic control that can be used as a predictor for the severity of developing retinopathy.